Trade Facilitation in Brazil: Bureaucracy and Compliance in the Port of Santos - Tavares Bertagnoli Wells, Simone; Tavares Bertagnoli Wells, Simone (2015)
This paper explores the topic of bureaucracy in maritime trade in the Port of Santos in Brazil considering the perspectives of compliance for firms. Considerable research was found on the grounds of bureaucracy in Brazil yet only a few of them associates the topic to maritime trade in Brazil, particularly when considering the entry of goods into the country; in other words, when goods are imported into Brazil.